Pengaruh Penundaan Waktu Pengeringan terhadap Mutu Benih dan Pertumbuhan Fase Vegetatif Padi (Oryza sativa linn.) Varietas Inpari 42 - Hatta Maulana Akhmad; Budi Wijayanto; Agus Wartapa (Universitas Sebelas Maret, 2022)
The study was conducted to determine the maximum delay of the proper drying time so that it does not affect the quality of rice seeds (Oryza sativa L. ) and can pass the quality testing of seed certification. This experiment used a Complete Randomized Design (CRD) using ten treatments and three replays; there were 30 experimental units. The results of the study were analyzed using ANOVA. Observations were made on the variables of moisture content before storage (%), moisture content after storage (%), germination (%), maximum growth potential (%), growing forging (%), plant height (cm), and numerous saplings. The results of the study showed no influence of the treatment of delayed drying time on the quality of rice seeds of the Inpari 42 variety. However, the moisture content increases with the long delay in drying time, germination power, maximum growing potential, and forging growth progressively decrease as the delay of drying time increases. The best results are obtained on the H0 treatment: the prospective seeds are immediately dried in the sun without storage after harvesting. The maximum drying time delay so that it can pass the seed quality test is six days after harvest. The delay in drying time does not affect the growth of the vegetative phase on the parameters of plant height and the number of saplings of 50 HSS.